2022
DOI: 10.3390/jpm12121953
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mindfulness and Positive Strengthening mHealth Interventions for the Promotion of Subjective Emotional Wellbeing and Management of Self-Efficacy for Chronic Cardiac Diseases

Abstract: Intervention in health prevention and treatment via mobile phones is becoming a key element on health promotion. Testing the efficacy of these mobile health (mHealth) psychological interventions for cardiovascular health is necessary as it is a chronic pathology, and it can influence the affective and cognitive states of patients. This research aimed to analyze the effectiveness of two brief psychological interventions—mindfulness and positive strengthening—to promote subjective emotional wellbeing and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In addition to self-esteem, self-e cacy is another key element of positive psychology that encourages a person to perform a particular task or behaviour successfully [42]. In this context, a previously published randomised clinical trial by Morone et al (2009) reported that a mindfulness intervention increased self-e cacy in the management of chronic low back pain in older people and in the selfmanagement of cardiovascular disease [45][46][47]. In addition, a study by Tsai et al (2023) showed that a mindfulness-based physical activity intervention in older people led to an increase in self-e cacy in preventing falls and a reduction in fear of falling, which had a positive impact on physical and physiological health [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to self-esteem, self-e cacy is another key element of positive psychology that encourages a person to perform a particular task or behaviour successfully [42]. In this context, a previously published randomised clinical trial by Morone et al (2009) reported that a mindfulness intervention increased self-e cacy in the management of chronic low back pain in older people and in the selfmanagement of cardiovascular disease [45][46][47]. In addition, a study by Tsai et al (2023) showed that a mindfulness-based physical activity intervention in older people led to an increase in self-e cacy in preventing falls and a reduction in fear of falling, which had a positive impact on physical and physiological health [48].…”
Section: Discussionmentioning
confidence: 99%